HUMIC SUBSTANCES ON TECHNOLOGICAL QUALITY OF SOME SUGARCANE VARIETIES - ROSATO, Marina Munhoz; BOLONHEZI, Antonio César; FERREIRA, Luiz Henrique Zuculo (Scientia Agraria, 2010)
As the sugarcane crop is occupying great areas in savannah soils, many of these areas can be characterized as stressful environments, it becomes inevitable the use of available technologies for the increment in sucrose. This study aimed to evaluate the influence of humic substances (SHs – humic acids – 0,12 kg kg-1; fulvic acids – 0,03 kg kg-1) applied in the planting furrow in the technological quality of the sugarcane. The experiment was conducted at Santa Terezinha Farm, located in Pereira Barreto, state São Paulo, Brazil. A randomized block design in a split plot scheme, containing 8 varieties: SP89-1115, SP81-3250, SP83-2847, SP91-3011, RB72454, RB867515, RB835054 and SP91-3440, treated or not with SHs, in four repetitions was used. The results showed that humic substances (SHs) were positive for variety SP91-3011 on sucrose accumulation; they promoted reduction in the glucose and fructose content of RB835054 and RB867515 varieties in certain times of the crop and, they did not affect the other technological characteristics of the sugarcane.